New Integral Transforms of the Extended k- Generalized Mittag-Leffler Function with Graphical Representations (European Journal of Pure and Applied Mathematics, 2024)
Different integral transforms have extensive applications in the various areas of science and engineering. Some of the new integral transforms of extended k-generalized Mittag-Leffler function are discussed in this paper. We examine integral transforms such as the Euler-Beta, Laplace, Mohand, Aboodh, SEE, and Sadik transform. Moreover, we also tried to establish the graphical representations of these transforms.